2008
DOI: 10.1007/s00431-008-0716-z
|View full text |Cite
|
Sign up to set email alerts
|

Anasarca: not a nephrotic syndrome but dermatomyositis

Abstract: Juvenile dermatomyositis (JDM) is a rare autoimmune disease characterized by inflammation of the muscle, connective tissue, skin, gastrointestinal tract, and small nerves. Periorbital and facial edema may also be associated. Although localized edema is a common feature of JDM, generalized edema has rarely been reported. Here, we report a 3.5-year-old boy with JDM presenting with generalized edema. The diagnostic criteria of JDM rely on typical clinical manifestations that include: severe symmetric weakness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…On the other hand, there are reports on patients with idiopathic inflammatory myopathies (DM, PM) who developed anasarca not related to nephrotic syndrome. 13,14 Gorelik et al, 15 for example, found seven cases of DM and PM related to anasarca in adult males, as described in the episode, and they also reported dysphagia in four of these patients. However, none of these patients progressed to nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, there are reports on patients with idiopathic inflammatory myopathies (DM, PM) who developed anasarca not related to nephrotic syndrome. 13,14 Gorelik et al, 15 for example, found seven cases of DM and PM related to anasarca in adult males, as described in the episode, and they also reported dysphagia in four of these patients. However, none of these patients progressed to nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 89%
“…We read with great interest the article by Dong et al on 'Upregulation of 78-kDa glucose-regulated protein in macrophages in peripheral joints of active ankylosing spondylitis' (1). In this work, Dong et al found that the endoplasmic reticulum (ER) chaperone glucoseregulated protein 78 (GRP78) is highly expressed in macrophages in the affected peripheral joints of ankylosing spondylitis (AS) compared with osteoarthritis (OA) patients.…”
Section: Accepted 5 November 2013mentioning
confidence: 95%
“…Periorbital oedema may be associated with this disease but generalized oedema is uncommon (1). Central nervous system (CNS) involvement and macrophage activation syndrome (MAS) are rarely reported in JDM (1,2). We present a case with both complications and an unusual presentation with severe generalized oedema.…”
mentioning
confidence: 95%
“…The striking feature in our case was anasarca. Such a presentation has been described with dermatomyositis before but not with polymyositis [4,5]. The weakness along with edema as well as the inability to get up from lying down position, indicating neck muscle involvement prompted us to suspect myositis.…”
mentioning
confidence: 96%
“…It is suggested that as a sequel to diffuse and widespread capillary endothelial damage, there is increase in capillary permeability in muscles leading to generalized edema [6]. At the presentation, initially, these cases may be misdiagnosed as nephritic syndrome [4,5].…”
mentioning
confidence: 99%